A comprehensive review on biodegradable polylactic acid polymer matrix composite material reinforced with synthetic and natural fibers. (2023) - Ashothaman, A.; Sudha, J.; Senthilkumar, N.
Abstract: Towards environmental sustainability and reducing the environmental degradation new materials are to be identified for usage in commercial and medical fields. Biodegradable polymers are the solution to that which reduces the effect of harmful polymers on environmental pollution. Polylactic acid (PLA) is the most broadly utilized ecological polymer but their limitations such as low glass transition temperature makes it unsuitable for high temperature applications and has low thermal stability and impact resistance than other polymers. In order to improve these properties reinforcements are done to improve their mechanical, thermal, wear and corrosion behavior thereby making it suitable for wider applications in automotive and biomedical applications. In this paper, an extensive review is being carried out to study the different fabrication methods, various reinforcements added to improve the mechanical performance of the various PLA based composites.